Comparing Total Fuel Consumption of A Ship Between East Asia And European Countries Travelling The Conventional Route Versus North-East Passage - Jürgen Siegl; Gerrit Tuschling; Reinhart Yosafat (International Journal of Marine Engineering Innovation and Research, 2018)
Global Warming is the most compelling environmental issues in the world recently. Almost a century, the temperature increased 0,74° Celsius and made the ice in North and South Pole melt in high rate.Some people say that global warming brings the negative effect for the society, however businessman, especially in shipping and logistic industries, believe that the melting ice process will shorten the distance between East Asia Countries and European Countries. Melting ice in Arctic Sea, open a new route, called Northeast Passage. Using Northeast Passage will reduce distance and time of the voyage.The big idea of this thesis is to compare 2 routes between Northeast Passage and Suez Canal for delivering cargoes from East Asia countries to European Countries or vice versa. Comparing total resistance, total fuel consumption and total cost for bunkering and additional charges are the main topic on this bachelor thesis.Results of this research, total fuel consumption for conventional route is 5810,231215 tons with operational hours of a vessel is 596,15 hours and the total fuel consumption per hour is 9,74625 tons/hour. By using Northeast Passage, a vessel can reduce 1900 nautical miles or saves 17% from the normal distance. There are 2 methods for calculating the resistance of the ship when passing through ice condition, Lindqvist and Riska method. If a vessel wants to save 20% of their fuel consumption (Lindqvist method: 4621,58 tons; Riska Method: 4670,82 tons) compared to conventional route, a vessel just only save 5% of their operational hour (needs 565,367 hours to travel Northeast Passage). Then, if a vessel wants to speed up and save 11% (528,03 hours) of the operational hour it reduces the saving of fuel consumption to 9% (Lindqvist Method 5270,615 tons; Riska Method 5322,38 tons).Bunkering Plan at conventional route is occurred at Hongkong Port, Port Klang and Piraeus Port with price 463 USD, 460 USD and 467 USD respectively. Suez Canal is controlled by a country so a vessel needs to pay some money for passing through the canal. The total price that needed to be paid for conventional route is 2.997.496,754 USD. Northeast Passage is considered as International water because there is too much complexity about the declaration. So, there is no taxes for a vessel when passing through the passage. Bunkering is occurred at Hamburg and one of Port in Russsian Coastline with price 447 USD at Hamburg and 400 USD at Russian. 1962466 USD needs to be paid for a vessel passing through Northeast Passage from Hamburg to Hongkong. The usage of Northeast Passage can saves 35% of expense or equivalent to 1035031 USD.